2023
DOI: 10.3390/cancers15184425
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and Therapeutic Significance of Tumor-Derived Extracellular Vesicles in Cancer Cell Migration and Metastasis

Giovanna L. Liguori,
Veronika Kralj-Iglič

Abstract: The infiltration of primary tumors and metastasis formation at distant sites strongly impact the prognosis and the quality of life of cancer patients. Current therapies including surgery, radiotherapy, and chemotherapy are limited in targeting the complex cell migration mechanisms responsible for cancer cell invasiveness and metastasis. A better understanding of these mechanisms and the development of new therapies are urgently needed. Extracellular vesicles (EVs) are lipid-enveloped particles involved in inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 202 publications
0
8
0
Order By: Relevance
“…Exosomes and microvesicles (EMV) are associated with tumor spread and chemotherapy resistance, through expelling drugs outside the cancer cells (Liu and Wang 2023 ). Their inhibition will enhance the accumulation of chemotherapy drugs inside the cancer cells and produce the same efficacy with the lower dose, accordingly potentiate the apoptosis in the cancer cells (Liguori and Kralj-Iglič 2023 ).…”
Section: Cannabis In Prostate Cancermentioning
confidence: 99%
“…Exosomes and microvesicles (EMV) are associated with tumor spread and chemotherapy resistance, through expelling drugs outside the cancer cells (Liu and Wang 2023 ). Their inhibition will enhance the accumulation of chemotherapy drugs inside the cancer cells and produce the same efficacy with the lower dose, accordingly potentiate the apoptosis in the cancer cells (Liguori and Kralj-Iglič 2023 ).…”
Section: Cannabis In Prostate Cancermentioning
confidence: 99%
“…GB cells have been shown to invade normal brain tissues, penetrating the brain parenchyma and the perivascular space by degrading the extracellular matrix through the release of proteolytic factors and by forming membrane-derived extensions known as invadopodia, which are involved in cell migration [64,65]. The patterns, directionality, and mechanisms responsible for this invasive behavior involve the extracellular matrix (ECM) and cytoskeletal remodeling, cell-to-cell and cell-to-ECM adhesion mechanisms, and the overall features of epithelial-mesenchymal transition (EMT).…”
Section: Invasiveness and Recurrencementioning
confidence: 99%
“…Several strategies have been identified that are based on targeting EVs on route (i.e., hemodialysis) or inhibiting EV release and uptake, including the use of natural substances (i.e., the antifungal agent ketoconazole or the alkaloid berberine extracted from herbal plants), as well as based on repurposed drugs such as heparin and reserpine, which are already used as anticoagulant and anti-hypertensive drugs, respectively [64,[90][91][92]. Alone, berberine, an efficient sensitizer used in PDT, can also suppress cancer cell proliferation by reducing the synthesis of fatty acids and inhibiting the formation and secretion of extracellular vesicles in cancer cells [91].…”
Section: Targeting Ev Biology and Cargomentioning
confidence: 99%
See 2 more Smart Citations